SUSTAINABILITY ASPECTS OF PROGRESSIVE CAVITY PUMPS USED IN OIL PRODUCTION - Marius STAN (Fiabilitate şi Durabilitate)
Pump, sucker rod and tubing string wear is directly proportional to the number of revolutions,therefore the use of larger displacement pumps operated at lower speeds can significantly extend equipmentlife. In order to reach the scope of paper is to have analyzed provided well data, well condition and wellconstruction and propose PC Pumping System to meet the applications production and lift requirements